2018
DOI: 10.1111/ijd.14217
|View full text |Cite
|
Sign up to set email alerts
|

Serum elafin as a potential inflammatory marker in psoriasis

Abstract: Elafin represents a mirror for psoriasis severity and inflammatory state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
(20 reference statements)
6
20
0
Order By: Relevance
“…In vitro, Lcn2 stimulated human neutrophils to produce proinflammatory mediators such as IL-6, IL-8, TNF-α, and IL-1α via a specific receptor, 24p3R, on neutrophils [60]. Elgharib et al showed statistically significant correlation between serum elafin levels and Psoriasis Area and Severity Index (PASI) score [61].…”
Section: Other Ampsmentioning
confidence: 99%
“…In vitro, Lcn2 stimulated human neutrophils to produce proinflammatory mediators such as IL-6, IL-8, TNF-α, and IL-1α via a specific receptor, 24p3R, on neutrophils [60]. Elgharib et al showed statistically significant correlation between serum elafin levels and Psoriasis Area and Severity Index (PASI) score [61].…”
Section: Other Ampsmentioning
confidence: 99%
“…The results presented by Elgharib et al were consistent with those of our research. The level of elafin was much higher in the patients than in the controls [23]. Alkemade et al also confirmed that the levels of serum and urine elafin were markers of psoriasis and the activity of the disease.…”
Section: Discussionmentioning
confidence: 86%
“…High circulating elafin levels reflect increased T cell-mediated immune activity. Similarly, circulating elafin levels are positively correlated with disease severity in patients with adaptive immune diseases (psoriasis and graft-vs-host disease) (Elgharib et al, 2019, Paczesny et al, 2010. Elafin-dependent IFN, IL-5, IL-12 p70, IL-2, IL-15, and TNF are not associated with the presence of intestinal strictures, suggesting that fibrogenesis are not driven by these elafin-dependent cytokines ( Figure 1E).…”
Section: Discussionmentioning
confidence: 90%